Financial Toxicity in Adolescents and Young Adults With Cancer: A Concept Analysis. Issue 6 (November 2021) - Ghazal, Lauren V.; Gormley, Maurade; Merriman, John D.; Santacroce, Sheila J.
Abstract : Background: A cancer diagnosis as an adolescent and young adult (AYA) poses exceptional challenges, including potential greater financial toxicity than older survivors experience who have had more time for career establishment and to build financial assets. Costs to patients have increased more than the past decade; prospects for AYA long-term survival have also increased. A better understanding of what financial toxicity is, how it presents, and the immediate and longer-term implications for AYAs is needed. Objective: The aim of this study was to analyze the concept financial toxicity in AYAs diagnosed with cancer. Methods: We used Rodgers' evolutionary method and articles published between January 2013 and December 2020. Results: We identified key antecedents, attributes, and consequences of financial toxicity in AYAs and review its related terms that have often been used as surrogate terms. Attributes were financial burden, financial distress, and competing financial pressures. Consequences were mostly adverse and persistent and included engaging in various financial problem-solving behaviors, material hardship and poor financial well-being, and deteriorated quality of life. Conclusions: Results of this analysis clarify financial toxicity and provide guidance for a conceptual framework in the context of AYA cancer survivorship. Its consequences in AYAs with cancer are profound and will continue to evolve over time with changes in health systems and the economy. Implications for Practice: Oncology nurses should understand the attributes and consequences of financial toxicity for AYAs throughout the cancer trajectory. Future research on financial toxicity should extend across AYAs living with other chronic illnesses and cancer survivors in other age groups.